18,63÷(2,2х+5,79)=23×0,1
18,63÷(2,2х+5,79)=2.3
18,63=2.3*(2,2х+5,79)
18.63=5.06x+13.317
5.06x=13.317-18.63
5.06x=-5.313
x=-5.313/5.06
x=-1.05
x = 1,05
Пошаговое объяснение:
18,63÷(2,2х+5,79)=2,3
2,2x + 5,79 = 18,63 ÷ 2,3
2,2x = 8,1 - 5,79
2,2x = 2,31
x = 2,31 ÷ 2,2
18,63÷(2,2х+5,79)=23×0,1
18,63÷(2,2х+5,79)=2.3
18,63=2.3*(2,2х+5,79)
18.63=5.06x+13.317
5.06x=13.317-18.63
5.06x=-5.313
x=-5.313/5.06
x=-1.05
x = 1,05
Пошаговое объяснение:
18,63÷(2,2х+5,79)=23×0,1
18,63÷(2,2х+5,79)=2,3
2,2x + 5,79 = 18,63 ÷ 2,3
2,2x = 8,1 - 5,79
2,2x = 2,31
x = 2,31 ÷ 2,2
x = 1,05